Acuerdo de promoción comercial entre la República de Colombia y Estados Unidos de América y su influencia en las exportaciones ecuatorianas al mercado estadounidense - Muñoz Caicedo, Patricio Eduardo (2015)
In recent years, the negotiation of trade agreements has been increased around the world, in most cases the countries which signs such agreements argue that they do so because of ensuring the entrance of their products, in favorable conditions, to its partner’s market. This was the case of Colombia, it signed an FTA with the US which is in force since June 2012. Scholars like Acosta and Falconi (2005), Cornejo (2006) and others have mentioned that to sign an FTA it involves not only benefits but also consequences for the signatory countries. Viner (2014) mentions that the creation of a free trade zone or customs union by signing an FTA, it produces changing in the trade flows between partner countries, as in the case of Colombia and the United States of America; and in third countries, as Ecuador. The propose of this work is to determine if once it be in force FTA between Colombia and the United States, trade diversion is shown from Ecuadorian products to Colombian products, it means if there is a change in the flow of exports Ecuador to the US market due to the aforementioned Agreement. By way of contextualization, it has addressed the issue of integration, and the arrangements and effects for finding the lines of argument to allow indicate whether there is a trade diversion or not. Subsequently, it has been analyzed the Trade Agreement between Colombia and the United States to determine the benefits which receive Colombian products in the US market. To check whether a trade diversion occurs, it has resorted to quantitative information on trade relations of the United States with Colombia and Ecuador, in order to determine which are the main products Colombian and Ecuadorian competing in the US market and, in turn, analyze their behavior to see if there is trade diversion to Colombian products.